ID 228 – Combining evoked potentials and EEG reactivity for coma prognosis. Issue 3 (March 2016) - Buisson, C.; Duclaux, M.; Hofmann, E.; Reynier, O.; Savarino, D.; Hatem, O.; Garcia-Larrea, L.
Abstract : The combined study of short- and long-latency responses remains restricted to a few university hospitals. Here we review results in 85 consecutive comatose patients (60% anoxic) studied with short- and long-latency AEPs and SEPs combined with EEG reactivity in a non-university hospital setting. We confirm the ominous prognosis associated with bilateral absence of brainsem and primary N20/Pa, whatever the coma atiology. Preservation of short-latency EPs does not have a significant positive predictive value, and was followed by death or PVS in 1/3rd cases. Presence of short- and long-latency responses (N20 + Pa + N100) had a strong positive predictive value for awakening from coma if they were associated with reactive EEG (85% of awakening). N100 and EEG reactivity were strongly associated; their dissociation (N100 present but non-reactive EEG) was followed in 6% of cases by vegetative state. Unilateral suppression of N20, with preservation of all other responses was associated with sensorimotor handicap on awakening. We underscore the prognostic usefulness of short + long-latency EPs + EEG in coma, and show its feasibility in non-university hospitals. The 85% ratio of awakening when N100 associates to reactive EEG stresses the importance of coupling the two measures for improving prognosis.